Influence of technological factors on the strength of wood adhesive joints - Ogrodniczek, Jacek; Rudawska, Anna; Miturska-Barańska, Izabela; Doluk, Elżbieta (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2022)
The article presents the results of a statistical analysis of adhesive joints with identical structural and material factors in relation to technological factors. Four types of adhesive joints were made: butt joints, lap joints, scarf joints and wedge joints. The joined materials were pine and oak wood. Each type of adhesive joint was joined in the following wood configurations: pine-pine, pine-oak, oak-oak. The technological factors were the type of adhesive, the humidity of the wood and the surface preparation of the samples. The U Mann-Whitney test was used to perform the statistical analysis. Results of statistical tests showed the influence of the used adhesive on pine-oak butt joints and wood moisture on pine-oak butt joints. Furthermore, the effect of wood configurations on the strength for each of the tested adhesive joints was compared using the Dunn’s statistical test. The test showed that there were not statistical differences between the joints in configurations pine-pine and pine-oak This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)